O ensino de Inglês na escola pública sob as lentes da interculturalidade: um breve recorte da realidade da cidade de Palmas (TO) - Santos, Ludmila Corrêa da Silva Honório e (2021)
The understanding that the English language can be a facilitator and mediator of intercultural encounters, has promoted discussions about less traditional and more critical attitudes and pedagogical practices that emphasize the importance of appreciating the culture of the other and one’s own. The textbooks approved by the federal government and made available to the country's public schools by the National Textbook Program (PNLD) are in line with this perception. This work observes, from an intercultural perspective, the relation between English teachers in some primary schools in Palmas-TO and the didactic material made available by PNLD / 2014. It also investigates how this relation reflects on the participants teaching practices. The literature used in this dissertation is founded on authors such as Baker (2009), Byram (2006, 2001), Cogo and Dewey (2012), Estermann (2010), Jenkins (2007), Kumaravadivelu (2003), Liddicoat and Scarino (2008), Rajagopalan (2010), Risager (2006), Seidlhofer (2005) and Siqueira (2008, 2010, 2012, 2013), to name a few. This research can be characterized as qualitative, of ethnographic and interpretative nature, having as research instruments an individual questionnaire, notes of class observation and a semi-structured nondirective interview with the participants. Regarding the results obtained, it is possible to observe that, despite the teachers' awareness of the importance of establishing opportunities for intercultural exchanges in their practices and their instrumental spaces, rarely were the moments when they became consolidated in the sense of enabling attitudes and behaviors free of cultural prejudices and stereotypes. The gap between theory and practice in the teaching of English was strongly highlighted, indicating that the establishing of a more conscious attitude about the political and social relevance of language teaching should require time and dedication in the sense of deconstructing an institutional model still based on traditional and hegemonic teaching practices. However, the participants showed awareness of the independent and liberating character of the language from an intercultural perspective.